The vocal and choral work of A. Gaidenko as a reflection of neo-folklore tendencies - Khaleeva, Olena; Ihnatieva, Yana; Tsekhmistro, Olga (My University, 2022)
The purpose of the article is a genre-style analysis of the vocal and symphonic works of the Kharkiv composer A. Gaidenko in the context of cultural and historical features of the modern author of the era. The article examines the cultural and historical prerequisites for the development of Ukrainian vocal and symphonic music of the last quarter of the twentieth century, which led to its synthesizing character and the principles of genre and style modeling in the vocal and symphonic work of Ukrainian composers, in particular A. Gaidenko. The research methodology is aimed at analyzing, identifying and understanding neofolklor trends and their reflection in the vocal and choral music of A. Gaidenko, in particular the cantata „Four acts”. The novelty of this scientific article lies in the fact that for the first time a systematic analysis of A. Gaidenko's vocal and symphonic work was carried out.
The vocal and choral work of A. Gaidenko as a reflection of neo-folklore tendencies / O. Khaleeva, Ya. Ihnatieva, O Tsekhmistro // Музикознавча думка Дніпропетровщини : зб. наук. статей. – Дніпро : Грані, 2022. – Вип. 22(1). – С. 83–94
Keywords: культурно-історичні передумови, вокально-симфонічна музика, кантатно-ораторіальний жанр, неофольклор; cultural and historical background, vocal and symphonic music, cantata and oratorio genre, neofolklore